Health Benefits of Pomegranate (Peel & Juice) and Preparation of Functional Pomegranate Drink Using Probiotic Lactobacillus Plantarum - Mai, M.M. Naeem (Food Technology Research Journal)
Pomegranate (Punica granatum L.) is rich in bioactive compounds, antioxidant, and volatile substances; under this investigates the impact of pomegranate peel (wastes), juice and preparation of probiotic juice by Lactobacillus plantarum on antimicrobial activity, antidiabetic in vitro and hypocholesterolemic agents by rats. Pomegranate peel extract has the highest total phenol, flavonoid and antioxidant more than juice .but no significance with probiotic juice. Antimicrobial compounds from pomegranate peel and probiotic juice are effective against a range of pathogenic microorganisms. The anti-amylase activity was significantly influenced by pomegranate tissues. The biological experiment used (n=36 rats up to 6 weeks) which were divided into six groups G1 (- ve control). G2 (positive control) by high-fat diet + 1% cholesterol, G3 (positive control+ 300 mg/kg/day/rat pomegranate peel extract), G4 (positive control+ 1 ml juice / day/rat), G5 (positive control+1 ml probiotic juice /day/rat), and G6 (positive control + reference drug 0.18 mg/kg/day/rat (ATOR 20 mg). Results, on the other hand, demonstrate the impact of peel extract, juice, and probiotic juice on lipid content (LDL, HDL, total cholesterol and triglycerides) and liver-related enzymes (ALT, ALP, AST). The pomegranate peel extracts and probiotic juice is more effective than juice due to the rich phenolic content and fermentation of juice by the probiotic strain Lactobacillus plantarum.